Modified nusinersen intrathecal injection method: inclusion of a septal needle-free closed infusion connector - Zhang, Yani; Zheng, Kelu; Liang, Cuili; Zheng, Ruidan; Chen, Jinghui; Jiang, Minyan; Zhou, Zhizi; Zhao, Yuan; Rao, Min; Yang, Sida; Chen, Wenxiong; Liu, Li (Frontiers in Neurology, 2023)
Objective Nusinersen, an extremely expensive biologic drug (around 100,000 US per dose) that needs to be administered intrathecally, is approved for the treatment of 5q-spinal muscular atrophy (SMA). Because of the low muscle tone of the back muscles of pediatric SMA patients, especially type 1 SMA patients, the safe, effective, and fast execution of sheath injection is needed. Therefore, a modified intrathecal injection method was developed accordingly. This paper aims to describe the applicability and safety of this modified method. Methods The modified intrathecal injection method (MIIM) mainly includes a septal needle-free closed infusion connector between the lumbar puncture needle and the syringe, besides the procedures of routine lumbar puncture. Its applicability and safety were evaluated through clinical observation. Results A total of 92 children with SMA have successfully received nusinersen treatment at our hospital using the modified method since 2019 without obvious adverse events related to the modified injection method. Based on the clinical feedback of operators, the advantages of the modified method include successfully injecting the total dose of nusinersen with constant injection rate and a more stable fixation of the puncture needle, as well as making the operator more relaxed. However, compared with the routine method, the procedure of the modified method has additional steps. Conclusion The modified intrathecal injection method is an effective and safe method to inject nusinersen when weighing the pros and cons, and it may also be used for administering intrathecal injections of other expensive medicines or for patients with other strict requirements for intrathecal injection.